PSYCHOANALYTIC STUDY OF SIGMUND FREUDS THEORY ON THE MAIN CHARACTER OF THE SANGKURIANG TALE ABOUT CHILD DEVELOPMENT - Arzeti, Febi (Jurnal Kopendik, 2023)
This research specifically discusses the main character, in this context represented by the Sangkuriang fairy tale to establish the principles of children's literature development based on developmental psychology. It is hoped that by examining current children's literature, principles of children's literature based on developmental psychology can be established, helping children develop the skills they need to succeed in the 21st century. Which in learning children experience difficulties in general, namely: learning difficulties in reading (dyslexia learning), in writing (dysgraphia learning) and difficulties in calculating (diyscalculia learning). The method used in this writing is qualitative research included in this study along with a literature review. With the results of the psychoanalytic theory developed by Sigmud Freud with the Sangkuriang fairy tale can improve difficulties in learning so that it is better.